Enforcement of Intellectual Property Law: Some Aspects of Trade in Counterfeit Goods in the Former Yugoslav Republic of Macedonia - Toshevska trpchevska, Katerina (WTO and WIPO, 2017)
This paper examines the enforcement of the customs law of the Former Yugoslav Republic of Macedonia on the protection of intellectual property rights (IPRs). The Customs Administration has the main role in the enforcement of intellectual property rights and in hampering the trade of counterfeit goods in the country. In order to step up the fight against trade in counterfeit goods and the protection of intellectual property rights in 2015, a new Law on Customs Measures for the Protection of Intellectual Property Rights was enacted. In addition, the number of registered customs officers that use the World Customs Organization (WCO) Interface Public-Members Platform has steadily risen. As a result of the increased involvement of the customs community in the protection of intellectual property rights, more goods have been temporarily retained under suspicion of violating intellectual property rights. This paper also highlights the rise in the sale of counterfeit products on the Internet, and the need for enhanced international cooperation in this area.
Keywords: enforcement of IP law, goods that violate IPRs, counterfeit goods, WCO Interface Public Members platform, customs seizures, online sale of counterfeit goods